Life in a time of COVID: retrospective examination of the association between physical activity and mental well-being in western Australians during and after lockdown - Ben Piggott; Paola Chivers; Kiira Karoliina Sarasjärvi; Ranila Bhoyroo; Michelle Lambert; Lynne Millar; Caroline Bulsara; Jim Codde (BMC Public Health, 2023)
Abstract Background The aim of this study was to examine physical activity and sedentary behaviours during Western Australia’s COVID-19 lockdown and their association with mental well-being. Methods Participants completed activity related questions approximately two months after a three-month lockdown (which formed part of a larger cross-sectional study from August to October 2020) as part of a 25-minute questionnaire adapted from the Western Australia Health and Well-being Surveillance system. Open-ended questions explored key issues relating to physical activity behaviours. Results During the lockdown period, 463 participants (female, n = 347; 75.3%) reported lower number of active days (W = 4.47 p < .001), higher non-work-related screen hours per week (W = 11.8 p < .001), and higher levels of sitting time (χ2=28.4 p < .001). Post lockdown body mass index was higher (U = 3.0 p = .003), with obese individuals reporting the highest non-work-related screen hours per week (Wald χ2= 8.9 p = .012). Inverse associations were found for mental well-being where higher lockdown scores of Kessler-10 (p = .011), Dass-21 anxiety (p = .027) and Dass-21 depression (p = .011) were associated with lower physical activity levels. A key qualitative message from participants was wanting to know how to stay healthy during lockdown. Conclusions Lockdown was associated with lower physical activity, higher non-work-related screen time and more sitting time compared to post lockdown which also reported higher body mass index. Lower levels of mental well-being were associated with lower physical activity levels during lockdown. Given the known positive affect of physical activity on mental well-being and obesity, and the detrimental associations shown in this study, a key public health message should be considered in an attempt to maintain healthy activity behaviours in future lockdowns and similar emergency situations to promote and maintain positive well-being. Furthermore, consideration should be given to the isolation of a community due to infectious disease outbreaks and to recognise the important role physical activity plays in maintaining weight and supporting good mental health.